Membrane vesicle production by Chlamydia trachomatis as an adaptive response - Frohlich, Kyla M.; Hua, Ziyu; Quayle, Alison J.; Wang, Jin; Lewis, Maria E.; Chou, Chau-wen; Luo, Miao; Buckner, Lyndsey R.; Shen, Li (Frontiers in Cellular and Infection Microbiology, 2014)
Bacteria have evolved specific adaptive responses to cope with changing environments. These adaptations include stress response phenotypes with dynamic modifications of the bacterial cell envelope and generation of membrane vesicles (MVs). The obligate intracellular bacterium, Chlamydia trachomatis, typically has a biphasic lifestyle, but can enter into an altered growth state typified by morphologically aberrant chlamydial forms, termed persistent growth forms, when induced by stress in vitro. How C. trachomatis can adapt to a persistent growth state in host epithelial cells in vivo is not well understood, but is an important question, since it extends the host-bacterial relationship in vitro and has thus been indicated as a survival mechanism in chronic chlamydial infections. Here, we review recent findings on the mechanistic aspects of bacterial adaptation to stress with a focus on how C. trachomatis remodels its envelope, produces MVs, and the potential important consequences of MV production with respect to host-pathogen interactions. Emerging data suggest that the generation of MVs may be an important mechanism for C. trachomatis intracellular survival of stress, and thus may aid in the establishment of a chronic infection in human genital epithelial cells.